2019
DOI: 10.1109/access.2019.2910830
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis and Mechanical Structure Improvement of Submersible Rotor

Abstract: In order to enhance interference immunity and reduce the breakage of rotating shafts (rotors) which happens frequently especially in submersible permanent magnet synchronous motor (PMSM) applications, first a typical rotor structure is established serving as the comparative object, and then two improved schemes with optimal mechanical structure are proposed. Rotor strength, rotor stiffness, and the influence of unilateral magnetic pull on the rotor deflection are calculated analytically. The modal simulation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Using uniformly distributed load of 5 N, tensile stresses and deflections were obtained for all cases. Many types of stresses and deflections in all directions for this shaft are obtained and discussed as following: In figures (3,4,5,6) when the eccentricity (e = 0.1x10 -3 ) the value of Von Mises stress (σ von ) begins from (33) Mpa at (N= 1000 R.P.M) and reach to (36.5) Mpa at (N= 4400 R.P.M) but (under the same conditions) in the case of the eccentricity (e = 0.3x10 -3 ) will be (43) Mpa at (N= 1000 R.P.M) and reach to (161) Mpa at (N= 4400 R.P.M). In figures (7,8,9,01), when the eccentricity (e = 0.1x10 -3 ) the value of (σ 3 ) stress begin from (-39.4) Mpa at (N= 1000 R.P.M) and reach to (-41.7) Pa at (N= 4400 R.P.M) but (under the same conditions) in the case the eccentricity (e = 0.3x10 -3 ) will be (-51.1) Mpa at (N= 1000 R.P.M) and reach to (-203) Mpa at (N= 4400 R.P.M).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using uniformly distributed load of 5 N, tensile stresses and deflections were obtained for all cases. Many types of stresses and deflections in all directions for this shaft are obtained and discussed as following: In figures (3,4,5,6) when the eccentricity (e = 0.1x10 -3 ) the value of Von Mises stress (σ von ) begins from (33) Mpa at (N= 1000 R.P.M) and reach to (36.5) Mpa at (N= 4400 R.P.M) but (under the same conditions) in the case of the eccentricity (e = 0.3x10 -3 ) will be (43) Mpa at (N= 1000 R.P.M) and reach to (161) Mpa at (N= 4400 R.P.M). In figures (7,8,9,01), when the eccentricity (e = 0.1x10 -3 ) the value of (σ 3 ) stress begin from (-39.4) Mpa at (N= 1000 R.P.M) and reach to (-41.7) Pa at (N= 4400 R.P.M) but (under the same conditions) in the case the eccentricity (e = 0.3x10 -3 ) will be (-51.1) Mpa at (N= 1000 R.P.M) and reach to (-203) Mpa at (N= 4400 R.P.M).…”
Section: Resultsmentioning
confidence: 99%
“…Also, they found a small effect of eccentricity distance on the stability of the rotor. Xiaohe Ran et ai [5] are enhance the shaft-rotor system by using two improvement schemes which are rotor stiffness, rotor strength as well as the effect of uni-lateral magnetic extension on the deflected rotor. They used finite element method (ANSYS) to modal, investigate stress and extended unilateral magnetic.…”
Section: ][2]mentioning
confidence: 99%
“…The paper showed that saturation effects, flow on the d and q axes, and other factors must be considered in analyses using the FEM to obtain accurate evaluated motor parameters. FEM analysis can also be used to improve the assessment of interference to reduce the breakdown of rotary axes in PMSM, by evaluating the stress to which the engine will be subjected through simulation [19]. In [20], the variation in the slots' design through an optimization process was also presented using the FEM for the design of a motorcycle engine equivalent.…”
Section: Introductionmentioning
confidence: 99%
“…A mechanical design of a PM motor with inside-out configuration for future 737 class hybrid-electric aircrafts was carried in [12]. To reduce the breakage of the rotating shaft for submersible PMSM, two improved schemes with optimal mechanical structures were proposed and verified in [13].…”
Section: Introductionmentioning
confidence: 99%